A Thrilling Case of Anemia - Mohammed Shanil P; Farsana Jasmin K (International Journal of Scientific Research in Science and Technology, 2024)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare bone marrow failure disorder that presents with triad of peripheral blood cytopenias, hemolytic anemia and thrombosis. The absence of two glycosylphosphatidylinositol (GPI)-anchored proteins, CD55 and CD59, leads to uncontrolled complement activation that accounts for hemolysis and other PNH manifestations. GPI anchor protein deficiency is due to acquired somatic mutations in phosphatidylinositol glycan class A (PIGA) gene.Terminal complement inhibition with eculizumab and allogeneic bone marrow transplantation (BMT) are the only widely effective therapies for patients with classical PNH. Compared to eculizumab and ravulizumab that block the fifth component of complement (C5), pegcetacoplan blocks the third component of complement (C3).
Keywords: Paroxysmal Nocturnal Hemoglobinuria; Glycosylphosphatidylinositol; Eculizumab; Ravulizumab; Pegcetacoplan